Massive pneumoretroperitoneum arising from emphysematous cholecystitis: a case report and the literature review. Issue 1 (December 2015) - Yagi, Yasumichi; Sasaki, Shozo; Terada, Itsuro; Yoshikawa, Akemi; Fukushima, Wataru; Kitagawa, Hirohisa; Fujimura, Takashi; Izumi, Ryohei; Saito, Katsuhiko
Abstract Background Emphysematous cholecystitis is a severe variant of acute cholecystitis caused by anaerobic bacteria. Although intraperitoneal air as a complication has been described in association with emphysematous cholecystitis, pneumoretroperitoneum arising from emphysematous cholecystitis is extremely rare. Herein, we describe a rare case of pneumoretroperitoneum arising from emphysematous cholecystitis that was successfully treated with emergency surgery. Case presentation An 84-year-old male was transported to the Emergency Department of our hospital for acute abdomen. Computed tomography revealed acute cholecystitis accompanied by emphysematous change. Computed tomography also revealed massive pneumoretroperitoneum complicated with pneumobilia and gas in the hepatoduodenal ligament. Clinical findings fulfilled the diagnostic criteria for systemic inflammatory response syndrome and sepsis. Emergency surgery was carried out with a diagnosis of both emphysematous cholecystitis and gastrointestinal perforation. Intraoperative findings revealed acute gangrenous cholecystitis and pneumoretroperitoneum presenting with an odor-free foamy abscess along the loose connective tissue behind the ascending colon and mesocolon. No evidence of gastrointestinal perforation was found during surgery. Therefore, cholecystectomy and lavage drainage were performed. Bacterial culture examination isolated a single species of anaerobe, Klebsiella pneumoniae, which was considered to be the cause of emphysematous cholecystitis, pneumobilia, and pneumoretroperitoneum. Conclusions Emphysematous cholecystitis should be considered as a possible cause of pneumoretroperitoneum. The present case is the first report of massive pneumoretroperitoneum extending to the dorsal side of the ascending mesocolon as a complication of emphysematous cholecystitis.